2009
DOI: 10.1007/s00213-009-1674-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine withdrawal and κ-opioid receptors

Abstract: These observations suggest that KOPr coupling and function are impaired in NAc and CPU during nicotine withdrawal, and imply receptor desensitization. KOPr desensitization might be a mechanism to ameliorate aversive behavioral symptoms, as nicotine withdrawal evolves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…The concomitant diminution of the ability of pCl-DPDPE to inhibit adenylyl cyclase in striatal membranes provides further support for DOPr uncoupling during nicotine withdrawal. The attenuated pCl-DPDPE-stimulated [ 35 S] GTPγS binding is unlikely to be caused by a decrease in G i/o proteins, as basal binding was not different among saline-and nicotine-treated mice at the times studied, and we have not found appreciable changes in the levels of G i1,2,3 and G o proteins in the striatum 24-72 h during nicotine withdrawal (McCarthy et al 2010). Loss of agonist activity, e.g., reduced [ 35 S]GTPγS binding, has been interpreted to indicate receptor desensitization at the Gprotein level (Harrison and Traynor 2003).…”
Section: Discussioncontrasting
confidence: 58%
“…The concomitant diminution of the ability of pCl-DPDPE to inhibit adenylyl cyclase in striatal membranes provides further support for DOPr uncoupling during nicotine withdrawal. The attenuated pCl-DPDPE-stimulated [ 35 S] GTPγS binding is unlikely to be caused by a decrease in G i/o proteins, as basal binding was not different among saline-and nicotine-treated mice at the times studied, and we have not found appreciable changes in the levels of G i1,2,3 and G o proteins in the striatum 24-72 h during nicotine withdrawal (McCarthy et al 2010). Loss of agonist activity, e.g., reduced [ 35 S]GTPγS binding, has been interpreted to indicate receptor desensitization at the Gprotein level (Harrison and Traynor 2003).…”
Section: Discussioncontrasting
confidence: 58%
“…Also, Isola et al (2008) reported that withdrawal from chronic nicotine injections diminishes striatal dynorphin content and enhances prodynorphin expression relative to saline-treated controls. Additionally, McCarthy et al (2009) found that striatal KOR coupling decreases over time after nicotine withdrawal, suggesting decreased KOR functionality is associated with the dissipation of nicotine withdrawal. Taken together, these studies support the role of KORs in mediating withdrawal from chronic nicotine exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, nor-BNI has been shown to block FSS- (Schindler et al, 2010) and U50,488-induced (McLaughlin et al, 2006) potentiation of cocaine-induced CPP, as well as, social defeat stress- (Land et al, 2009), FSS-, and U50,488-induced (Redila and Chavkin, 2008) reinstatement of cocaine-induced CPP. Furthermore, KOR activation is enhanced in limbic brain regions during nicotine withdrawal (Isola et al, 2008; McCarthy et al, 2010). This suggests that KORs may be a promising focus for the development of therapies to treat or prevent relapse.…”
Section: Discussionmentioning
confidence: 99%